BRIEF: Bulls to put T-Mac through the paces: Bu haven't made a decision to sign the veteran free agent - Johnson, K C (McClatchy - Tribune Business News, 2010)
McGrady, a seven-time All-Star, is trying to find a home after playing just 30 games last season because of microfracture surgery on his left knee in February 2009.